Load cell-based PID method controlled Segway system modelling and simulation. (17th December 2021) - Kelek, Muhammed Mustafa; Fidan, Ugur; Oguz, Yuksel; Celik, Ibrahim; Ozer, Tolga
In the present study, mathematical modelling and simulation of load cell-based Segway has been done. Four load cells placed on the Segway to provide the control of the system. According to the measured weight information, the dynamic model of the system can be updated instantly. This operation makes the Segway control easier by changing the maximum pitch angle. In order for the system to stay in balance on two wheels, it must move at the appropriate pitching angle and at the desired speed. The control of the suitable pitching angle and speed are controlled by the PID method. As a result of the simulation in Matlab/Simulink environment, Segway's speed information, current information of BLDC and pitching angle can be accessed. As a result of the study, it is thought that the load cell-based Segway can be controlled more effectively.